Analisis Implementasi Kebijakan Penurunan Stunting di Kabupaten Lombok Tengah Provinsi Nusa Tenggara Barat - St. Khadijah; Milwan Milwan; Rulinawaty Rulinawaty (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Stunting remains a major public health issue affecting child growth and human capital quality, requiring sustained cross-sectoral interventions. Central Lombok Regency has recorded one of the highest stunting prevalence rates in West Nusa Tenggara Province, although recent data indicate a declining trend. This study aims to analyze the effectiveness of stunting reduction policy implementation, identify influencing factors, and formulate improvement strategies. A descriptive qualitative approach was employed using purposive and accidental sampling techniques. Informants included relevant government agencies, health workers, and community members. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using Edward III’s policy implementation model focusing on communication, resources, disposition, and bureaucratic structure. The findings reveal that policy implementation is relatively effective, supported by cross-sector coordination through acceleration teams, stunting forums, and the utilization of nutrition reporting systems. However, effectiveness remains suboptimal due to limited resources, particularly budget constraints, implementer capacity, data quality, and measurement tools. External factors such as socio-economic conditions and socio-cultural characteristics also influence community health behaviors. The study concludes that strengthening policy implementation requires improving human resource capacity, enhancing data systems, simplifying reporting mechanisms, and developing more adaptive and context-specific intervention strategies. These efforts are essential to ensure sustainable stunting reduction outcomes. The study implies that stronger integration across sectors, data-driven monitoring and evaluation, and increased community participation are critical to accelerating progress toward stunting reduction targets. Furthermore, policy alignment between local and national levels is necessary to ensure consistency, effectiveness, and long-term sustainability of stunting prevention programs in diverse regional contexts..